PELATIHAN PEMBUATAN PEMBUKUAN SEDERHANA UNTUK MENINGKATKAN KINERJA UMKM - Abdullah Syakur Novianto; Yuzky Maulana Irbad; Kusumas Tutik Wahyuningsah; Ermawati Ermawati; Nita Prihatiningrum; Sahla Ramli; Hambali Hambali; Aan Irawan; Arif Ruri Abdillah; Basyaruddin Faizal Rafi; Sahrul Hidayatullah; Arif Rahwansyah (Universitas Islam Malang, 2022)
Bookkeeping is indispensable to find and measure the performance of MSMEs. MSME Fandafa Group, which is located in Pungging Village, Tutur District, Pasuruan Regency, still uses the manual recording method so it has not been well structured. This makes it difficult for business activities to develop properly. Based on these problems, KSM-Thematic Group 101 conducted training in making simple bookkeeping. This training aims to provide guidance for the MSMEs of the Fandafa Group to optimize profitability, operational analysis and the level of control, control and decision making. The method used begins by explaining the material and the importance of simple bookkeeping. The next stage is training in simple bookkeeping consisting of a cash book, inventory of goods, inventory of goods and income statement. The result of this training is that Fandafa Group knows the importance and how to make financial reports for the Fandafa Group to be more structured so that it can analyze business performance which in the end Fandafa Group can optimize its performance.